Gaya Hidup Investor Perempuan Modern di Kota Palembang - Lemiyana Lemiyana (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2019)
This study aims to examine how much influence the lifestyle of modern female investors in the Indonesia Stock Exchange in the city of Palembang. The object of this research is the Women's Investor in the Indonesian Stock Exchange capital market in Palembang City. The sample collection method uses non-probability sampling techniques and sampling techniques based on judgmental sampling. Samples were taken as many as 150 female investors in the city of Palembang. Test data analysis using Structural Equation Model (SEM) software.The results of the tests that have been carried out show that: first, the investment variable has a positive and significant effect on the variable of modern female investors in the Indonesia Stock Exchange in Palembang City. Second, the Lifestyle variable influences the variable of modern female investors in the Indonesia Stock Exchange in Palembang City